Genetic outcomes of translocation of bighorn sheep in Arizona. Issue 4 (5th March 2019) - Gille, Daphne A.; Buchalski, Michael R.; Conrad, Dave; Rubin, Esther S.; Munig, Amber; Wakeling, Brian F.; Epps, Clinton W.; Creech, Tyler G.; Crowhurst, Rachel; Holton, Brandon; Monello, Ryan; Boyce, Walter M.; et al.
ABSTRACT: Translocation is an important management tool that has been used for >50 years in Arizona, USA, to increase bighorn sheep ( Ovis canadensis ) population densities and to restore herds to suitable habitat throughout their historical range. Yet, translocation can also alter the underlying genetic diversity and spatial structure of managed wildlife species in beneficial or detrimental ways. To evaluate the long‐term effect of translocation actions on bighorn sheep, we characterized statewide genetic structure and diversity using microsatellite and mitochondrial DNA data in 16 indigenous and translocated (supplemented or reintroduced) Arizona populations sampled between 2005 and 2012. Populations that were recipients of translocated animals showed no reduction in genetic diversity with allelic richness and heterozygosity estimates equivalent to, and in some cases greater than, indigenous source populations. The indigenous population occupying the Silver Bell Mountains population displayed the lowest indices of genetic diversity but shared mitochondrial DNA haplotypes with the Mohawk Mountains, Sierra Pinta, and Cabeza Prieta populations, indicating past connectivity and potential opportunities for genetic management if warranted. Bayesian clustering on genetic similarity and genetic divergence estimates corroborated previous work differentiating Rocky Mountain bighorn sheep ( O. c. canadensis ) and 2 desert lineages corresponding with Nelson's ( O. c. nelsoni ) and Mexican desert bighorn sheep ( O. c. mexicana ). In northern Arizona, assignment tests confirmed the presence of 2 indigenous metapopulations of Nelson's desert bighorn sheep in the Black Mountains and Grand Canyon and indicated that gene flow from the Grand Canyon population has likely played a role in maintaining genetic diversity and mitigating founder effects among multiple translocated populations in the area. In southern Arizona, we detected genetic structure consistent with 2 metapopulations of Mexican desert bighorn sheep representing a departure from current management practices that consider this lineage to be a single genetic unit. Several lines of genetic evidence presented in this study suggest that the Bill Williams River area is the contemporary contact zone for the 2 desert lineages; however, the degree to which translocation has enhanced introgression is unknown. Despite relative isolation from other herds, the translocated Rocky Mountain bighorn sheep population in eastern Arizona had high levels of allelic richness and heterozygosity and a negative inbreeding coefficient, conceivably as a result of multiple translocation events from sources in Colorado and New Mexico, USA. Although translocation management has successfully contributed to the reestablishment of bighorn sheep populations in Arizona without diminishing genetic diversity, future translocation should proceed with caution to preserve the genetic integrity and potential local adaptation within the Nelson's and Mexican desert bighorn sheep metapopulations identified in this study. © 2019 The Wildlife Society. Abstract : We evaluated microsatellite and mitochondrial DNA diversity in indigenous and translocated populations of bighorn sheep in Arizona to assess the genetic outcomes of over half a century of translocation management. Our study revealed that there was no reduction in genetic diversity of translocated populations compared to sources and that previously undetected hierarchical genetic structure was present within 2 desert bighorn sheep ancestral lineages.